A cross-sectional study on the concordance between vaginal HPV DNA detection and type-specific antibodies in a multi-ethnic cohort of women from Amsterdam, the Netherlands – the HELIUS study. Issue 1 (December 2016) - Kovaleva, Alexandra; Alberts, Catharina; Waterboer, Tim; Michel, Angelika; Snijder, Marieke; Vermeulen, Wilma; Coyer, Liza; Prins, Maria; Schim van der Loeff, Maarten
Abstract Background Acquisition of genital human papillomavirus (HPV) infection is common among the young, sexually active population. Genital HPV infections do not always lead to seroconversion. We aimed to assess the association between cervico-vaginal high risk (hr) HPV DNA and type-specific antibodies in an ethnically diverse cohort of young women. Methods Women of Dutch, South-Asian Surinamese, African Surinamese, Ghanaian, Moroccan and Turkish origin participating in a large-scale multi-ethnic population-based cohort (the HELIUS study) provided vaginal self-samples and blood samples, and completed a questionnaire regarding demographics, lifestyle and sexual health. Vaginal swabs were tested for HPV using the highly sensitive SPF10-PCR DEIA/LiPA25 system (version1). Serum samples were tested for type-specific L1 antibodies against 7 hrHPV types (16, 18, 31, 33, 45, 52, 58) with multiplex serology. We assessed the association between vaginal HPV DNA and type-specific seropositivity with logistic and linear regression, using generalized estimating equations (GEE). We determined whether this association varies by ethnicity by adding an interaction term. Results We selected 532 women who completed the questionnaire, provided a vaginal swab and a blood sample. Their median age was 27 years (interquartile range 24–31 years). Prevalence of DNA of any of the 7 hrHPV was 22 %; HPV-52 was most common. Prevalence of antibodies against one or more hrHPV types was 24 %; HPV-16 seropositivity was most common. In multivariable logistic regression analysis using GEE, adjusting for other determinants, vaginal HPV DNA detection was associated with type-specific HPV seropositivity (OR 1.53, 95 % CI 1.06-2.20). In multivariable linear regression analysis using GEE, the geometric mean of type-specific antibody reactivity was 1.15 (95 % CI 1.04-1.27) times higher in women positive for HPV DNA compared to HPV DNA-negative women. There was little evidence that ethnicity modified the association between HPV DNA, and type-specific seropositivity, or with antibody reactivities (p = 0.47 andp = 0.57, respectively). Conclusions In this multi-ethnic group of young women in Amsterdam, cervico-vaginal hrHPV DNA detection was an independent determinant of type-specific HPV seropositivity.